Perancangan Interior Auditorium di Surabaya - Riyanto Sulistio (Intra, 2013)
Auditorium project in Surabaya is engaged in the arts, particularly the art of music. facilities planned include a standardized auditorium, backstage, and do not forget the cafe shop. Art music favored by many people from the young to the elderly with a wide range of music. So the theme of this design refers to the complex nature and can not be guessed that the theme of "Music". Therefore, in designing the interior of the auditorium to use your many formations arch, a square and a line to be composed with the function of the room, so the only interesting in terms of the interior is also